MOTIVASI BELAJAR DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR SISWA - Astrid Harera, ; Imam Setiyono, (Pendidikan Ekonomi, 2013)
The study aims to find out whether the learning motivation and the parental attention give the partial or simultaneous effect to the learning outcomes on X grade students in SMA Muhammadiyah 4 Surabaya. The type of the research is associative with quantitative approach, since the purpose of the study is to find out the impact of those two variables. The result of the study showed that the learning motivation variable (X1) is 0,8684 and parental attention variable (X2) is 0,6736, it can be concluded that partially the learning motivation and the parental attention significantly influenced students learning outcomes. While the F test result is 0,905437, it can be concluded that simultaneously the students motivation and the parental attention influence their learning outcomes significantly.